2022
DOI: 10.1186/s13052-022-01372-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of ursodeoxycholic acid in neonatal indirect hyperbilirubinemia: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Neonatal jaundice is a transitional phenomenon affecting three out of five full-term newborns globally. Ursodeoxycholic acid could be beneficial in neonatal jaundice needing phototherapy.  Methods We searched PubMed, EBSCO, ProQuest, and Cochrane Library up to August 21st, 2021, for articles to be reviewed. Meta-analysis using random-effects model was performed. Results Eight studies involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
5
0
5
Order By: Relevance
“…Instead, a recent meta-analysis by Lazarus et al concluded that UDCA with PT was effective in reducing the Pt duration and reducing the TSB levels. 36 There are several hypotheses related to how UDCA may reduce the UCB. For example, Cuperus et al 37 on the enterohepatic recirculation of UCB and increased fecal secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a recent meta-analysis by Lazarus et al concluded that UDCA with PT was effective in reducing the Pt duration and reducing the TSB levels. 36 There are several hypotheses related to how UDCA may reduce the UCB. For example, Cuperus et al 37 on the enterohepatic recirculation of UCB and increased fecal secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Полнота систематических обзоров определялась наличием среди всех включенных в обзор исследований всех идентифицированных в рамках текущего проекта исследований [13]. Обзор признан полным, если все идентифицированные, подходящие и опубликованные Характеристика систематических обзоров Обзоры выполнены авторами из Финляндии (Kuitunen I. и соавт., 2022) [16 ], Италии (Lazarus G. и соавт., 2022) [17 ], Саудовской Аравии (Huseynova R.A., 2022) [18 ] и Китая (Wang G. и соавт., 2023) [19 ]. Во всех обзорах оценено влияние УДХК в сочетании с фототерапией на уровень общего сывороточного билирубина, продолжительность фототерапии и частоту нежелательных явлений в сравнении с фототерапией ± плацебо при гипербилирубинемии у доношенных [17 , 18] или доношенных и поздних недоношенных детей [16 , 19] без факторов риска.…”
Section: оценка актуальности и полноты систематических обзоровunclassified
“…A meta-analysis evaluates, in case of neonatal indirect hyperbilirubinemia in treatment with phototherapy, the use of ursodeoxycholic acid as adjunctive therapy [140]. Ursodeoxycholic acid is classically used for the management of cholestatic liver pathology through increased production of bile, the removal of the most toxic components of bile acids and additional hepatoprotective and neuroprotective effects [141][142][143].…”
Section: -Hyperbilirubinemiamentioning
confidence: 99%